The complete mitochondrial genome of the devil firefish Pterois miles (Bennett, 1828) (Scorpaenidae). (2nd January 2016) - Dray, Liran; Neuhof, Moran; Diamant, Arik; Huchon, Dorothée
Abstract: The complete mitochondrial genome of the devil firefish Pterois miles (Bennett, 1828) was obtained using next generation sequencing approaches. The genome sequence was comprised of 16, 497 bp exhibiting the standard vertebrate mitochondrial gene arrangement. Regions of gene overlap, tRNA lengths, as well as start and stop codons were similar to those observed in closely related families (i.e. Sebastidae, Peristediidae). Phylogenetic reconstructions support the polyphyly of Scorpaeniformes, and confirm the close relationship of Scorpaenidae and Sebastidae.